Consumer perception on the multi-use lightweight polypropylene raw meat containers - Cuarto, Shekainah R.
Polypropylene containers are widely used in the food packaging industry given their suitability and tensile strength, making it resistant to unfavorable conditions. Despite being marketed as disposable, reusing lightweight PP containers (LPCs) is already accustomed in Philippine households for various reasons including the mitigation of environmental concerns. However, the multi-use of LPCs used as packaging for raw meat might pose a risk to health due to cross-contamination. This study aims to provide insights into the perception of consumers on the threat of the multi-use of LPCs used for raw meat through administering an online survey which aims to assess the knowledge, self-reported behaviors, and psychosocial aspects of consumers of LPCS used for raw meat (n=100), followed by a Focus Group Discussion (FGD) to further elaborate the survey findings (n=10). Participants correctly answered 83.3% of the knowledge questions which shows that they are knowledgeable about most food safety concepts. Meanwhile, only 46.1% of the behavior questions were answered with ‘best practices’ by the participants. Inferential analysis shows that there is no correlation between the high knowledge scores and self-reported practices of consumers, which suggests that there is a lack of application of knowledge when handling LPCs used for raw meat. Moreover, participants had positive food safety beliefs, confidence in their food safety knowledge and practices, and attitude towards the multi-use of LPCs used for raw meat. Using ordinal regression, it was determined that the variables that significantly affect the behavior of consumers are the reusing and disposing observations, familiarity with reusing, availability, and their own preference to dispose LPCs used for raw meat. Efforts to improve risk perception, and ultimately, the food safety practices of consumers when handling LPCs are essential to ensure that consumers would not engage in risky practices. Establishing good food safety measures in terms of handling LPCs and raw meats through food safety education should also take part in future communication strategies.